Réponses

2014-09-07T12:32:46+02:00
A = -2/3 + 1/6 x 2
A = -2/3 + 2/6
A = - 4/6 + 2/6 = - 2/6 = -1/3

B = 2/5 x 1/3 + 4/15
B = 2/15 + 4/15 = 6/15

C = 1/7 - 1/7 x 1/2
C = 1/7 - 1/14
c = 2/14 - 1/14 = 1/14

D = 6/5 x ( (1/2 - 1/3)
D = 6/5 x ( 3/6 - 2/6)
D = 6/5 x 1/6
D = 6/30 ou 1/5
2014-09-07T12:34:59+02:00
A = - 2/3 + 1/6 x 2
A = - 2/3 + 2/6
A = - 2 x 2 / 3 x 2 + 2/6
A = - 4/6 + 2/6
A = - 2/6
A = 2 x - 1 / 2 x 3
A = - 1/3

B = 2/5 x 1/3 + 4/15
B  = 2/15 + 4/15
B = 6/15
B = 3 x 2 / 3 x 5
B = 2/5

C = 1/7 - 1/7 x 1/2
C = 1/7 - 1/14
C = 1 x 2 / 7 x 2 - 1/14
C = 2/14 - 1/14
C = 1/14

D = 6/5 x (1/2 - 1/3)
D = 6/5 x (1 x 3 / 2 x 3 - 1 x 2 / 3 x 2)
D = 6/5 x (3/6 - 2/6)
D = 6/5 x 1/6
D = 6/30
D = 6 x 1 / 6 x 5
D = 1/5